The Effect Of Tax Planning And Net Profit Margin On Company Value In Plantation Companies Listed On The Idx In 2020 - 2024 - Anggita Sari Rangkuti; Novien Rialdy (Institute of Advanced Knowledge and Science, 2024)
This study aims to determine the effect of tax planning and net profit margin on plantation companies listed on the Indonesia Stock Exchange in 2020 - 2024. This study is an associative type of research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained was 11 plantation companies listed on the IDX in 2020 - 2024 with a total of 55 observation data for 5 years of observation. The data collection technique used was documentation. The data analysis technique used in this study was multiple linear regression analysis with SPSS 26 software tools. The results of the tax planning study showed a statistical test value of t count of 1.633 smaller than t table of 2.006 while the sig value of tax planning was 0.112 greater than 0.05, this indicates that tax planning has no effect on company value. Net profit margin shows a statistical test value of t count of 2.465 greater than the t table of 2.006 while the sig value of net profit margin of 0.019 is smaller than 0.050, this shows that net profit margin affects the value of the company. The results of the study of tax planning and net profit margin together show a statistical value of F count of 5.879 greater than the F table value of 3.280 while the sig value of 0.006 is smaller than 0.05, this shows a significant influence between tax planning and net profit margin on the value of the company simultaneously.